2020
DOI: 10.1016/j.metop.2020.100029
|View full text |Cite
|
Sign up to set email alerts
|

Launaea taraxacifolia leaf partitions ameliorate alloxan-induced pathophysiological complications via antioxidant mechanisms in diabetic rats

Abstract: Launaea taraxacifolia (Wild.) Amin ex. Jeffery belongs to family Asteracaea. The plant is used for treatment of diseases and eaten as vegetable in Nigeria. This study investigated the ameliorative potentials of L . taraxacifolia leaf partitions in alloxan induced diabetic complications. Male Albino rats were divided into eleven groups of five rats each. Diabetes was induced following intraperitoneal administration of 150 mg/kg alloxan monohydrate and was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Moreover, the L. nudicaulis extract was found to improve the renal functions including that deduced via enhancement of creatinine, uric acid, and urea compared with glibenclamide. All these data are in full agreement with Gbadmosi, et al’s results [ 61 ]. All the results revealed to the capability of the extract to manage the serum insulin levels along with the weekly body weight.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, the L. nudicaulis extract was found to improve the renal functions including that deduced via enhancement of creatinine, uric acid, and urea compared with glibenclamide. All these data are in full agreement with Gbadmosi, et al’s results [ 61 ]. All the results revealed to the capability of the extract to manage the serum insulin levels along with the weekly body weight.…”
Section: Resultssupporting
confidence: 92%
“…The reduction of the blood glucose levels via the effect of the extract induction might be ascribed to its capacity to increase glucose absorption as well as the decreasing of the glucagon releasing (11). All these effects were documented from several medicinal plants including some Launaea plants such as L. taraxacifolia and L. cornuta [61]. Also, the inhibitory action of the extract of α-glucosidase might be one of the possible mechanismatic pathways that increase the polysaccharide conversion to simple sugars [62].…”
Section: Nitrogenous Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was further substantiated by histology findings, which showed that diabetic groups displayed shrinkage, necrosis, and damaged β-cell populations; however, after administering LUT, these effects returned to normal. We found an interesting agreement between our findings and recently published reports [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…The LUT treatment for diabetic rats possessed insulin-secretory effects like GLB [ 24 ]. These findings showed that LUT can reduce insulin resistance in diabetic animals [ 25 , 26 ]. This was further substantiated by histology findings, which showed that diabetic groups displayed shrinkage, necrosis, and damaged β-cell populations; however, after administering LUT, these effects returned to normal.…”
Section: Discussionmentioning
confidence: 99%